(untitled) (Eurasian Research Bulletin, 2023)
Among the poetic forms of Uzbek classical literature, stanza poems are of particular importance. The poem forms, which differ according to the number of verses in the stanza, are united under the term musammat, which is derived from the Arabic word "tasmit", which means "string of pearls". , means "to string pearls on a string". This article talks about busy poems, including mukhammas.